THE STUDENTS’ PERCEPTIONS ON THE USE OF MOBILE-ASSISTED LANGUAGE LEARNING THROUGH DUOLINGO IN IMPROVING VOCABULARY MASTERY AT THE TERTIARY LEVEL - Alfaruqi Alalwani Dunggio; Tri Wintolo Apoko; Su Li Chong (English Review: Journal of English Education, 2023)
The use of Duolingo as one of free online applications by students in learning English is essential. More studies on Duolingo app were conducted. However, in the context of university students of Indonesia in improving vocabulary mastery in the online learning setting, this current study was rare. This research was aimed to investigate the students’ perceptions on Mobile-Assisted Language Learning through Duolingo Apps to improve vocabulary mastery. The research used a mixed method.  There were 95 undergraduate students from some private and public universities in Indonesia. Online questionnaire and semi-structure interview were conducted to collect the data. The finding revealed that Duolingo apps improved the students’ vocabulary mastery in their English learning. It is then recommended that Duolingo be used for EFL and non-EFL students in the university to increase their English proficiency, mainly in vocabulary mastery as it is simple, easy to use, and available to access. In addition, it provides interesting and informative features. Therefore, it implies that Duolingo promotes the students’ willingness and motivations to practice English better.